The Asian economic catharsis : how Asian firms bounce back from crisis - Richter, Frank-Jürgen (Quorum, 2000)
Annotation "An important resource for professionals in all multinational organizations, Richter's book will have special value for academics and upper level university students of international business."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved